2019
DOI: 10.4103/bc.bc_7_19
|View full text |Cite
|
Sign up to set email alerts
|

The neuroprotective mechanisms and effects of sulforaphane

Abstract: Sulforaphane (SFN) is a phytochemical found in cruciferous vegetables. It has been shown to have many protective effects against many diseases, including multiple types of cancer. SFN is a potent activator of the nuclear factor erythroid 2-related factor 2 (Nrf2) antioxidant response element (ARE) genetic pathway. Upregulation of Nrf2-ARE increases the availability of multiple antioxidants. A substantial amount of preclinical research regarding the ability of SFN to protect the nervous system from many disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 72 publications
(169 reference statements)
0
14
0
Order By: Relevance
“…Sulforaphane (SFN) is found in highest concentrations in vegetables such as cauliflower and broccoli sprouts, and it has been shown that SFN is an activator of nuclear factor erythroid 2-related factor 2 (Nrf2) [52]. Nrf2 is a transcription factor widely recognized as a master regulator of cellular redox homeostasis [53,54].…”
Section: Sulforaphane Exerts Anti-inflammatory Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Sulforaphane (SFN) is found in highest concentrations in vegetables such as cauliflower and broccoli sprouts, and it has been shown that SFN is an activator of nuclear factor erythroid 2-related factor 2 (Nrf2) [52]. Nrf2 is a transcription factor widely recognized as a master regulator of cellular redox homeostasis [53,54].…”
Section: Sulforaphane Exerts Anti-inflammatory Activitymentioning
confidence: 99%
“…Action mechanisms of antioxidants used against inflammation are shown in Figure 2. actor 2 (Nrf2) [52]. Nrf2 is a transcription factor widely recognized as a master regulator of cellu edox homeostasis [53,54].…”
Section: Sulforaphane Exerts Anti-inflammatory Activitymentioning
confidence: 99%
“…15,16) Furthermore, certain Nrf2 activator was reported to fail to increase the protein levels of γ-GCS and NQO1, although the mRNA levels of them were upregulated. 17) Sulforaphane is not only a powerful antioxidant phytochemical but also anti-inflammatory phytochemical with great promise in its ability to protect the nervous system from many diseases and toxins and reduce the symptomatic burden of multiple pervasive diseases. 18) There is a possibility that unknown factors should be involved in DDC-induced upregulation of HO-1 in HaCaT cells in addition to Nrf2-ARE pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, sulforaphane given to autistic children improve their behavioral phenotype. Moreover, although the mechanism of action is not known, sulforaphane is described as modulating oxidative stress, methylation, or apoptosis, and to be a potent neuroprotective molecule [170][171][172][173][174]. Overall, the identification of this molecule supports a beneficial role of low GI diet in ASD.…”
Section: Others: Dementia Depression Mental Health…mentioning
confidence: 95%